Korelasi antara Imunoekspresi LMP-1 Virus Epstein-Barr dengan Respon Kemoterapi CHOP pada Limfoma Maligna Non-Hodgkin Tipe Diffuse Large B Cell. - Inas Susanti; Hasrayati Agustina; Bethy S Hernowo (Majalah Patologi Indonesia, 2016)
Background Diffuse large B cell lymphoma is the most common type of B-cell non-Hodgkin malignant lymphoma. Epstein-Barr virus (EBV) has been shown to contribute to the development of this tumor especially in the elderly patient (above 50 years). The chemotherapeutic agents CHOP (Cyclophospamide, Hydroxydaunorubicin, Oncovin, Prednison) are standard treatment for non-Hodgkin lymphoma patients, but approximately 30% cases shows non-respone with standard chemotherapy and undergoes progressive disease until death. There are no accurate predictor factors in predicting CHOP chemotherapy respone in patients with DLBCL. The aim of this study is to determine the role of LMP-1 in predicting CHOP chemotherapy respone in patients with DLBCL. Methods This study was done retrospectively in 34 cases of DLBCL. The samples were obtained from the Anatomic Pathology Department of Dr. Hasan Sadikin Hospital from January 2009 to Desember 2011. All cases were reviewed for histopathological diagnoses based on the WHO Classification of 2001 and the specimens were stained with specific antibodies against CD 20 (for diagnoses DLBCL) and LMP-1. The data were analized using rank Spearman’s correlation test. Results This study showed that 31 cases (91.18%) were LMP-1 positive, only 3 cases (8.82%) were negative. Three cases of negative LMP-1 had a good respone to chemotherapy, whereas among 31 positive cases LMP-1 showed good respone to chemotherapy in 21 cases and the remaining 10 cases had a poor respone to chemotherapy. There was no correlation between EBV-LMP-1 immunoexpression with CHOP chemotherapy respone in DLBCL (p=0.436). Conclusion There was no correlation between EBV-LMP-1 immunoexpression with CHOP chemotherapy respone in DLBCL. Key words: CHOP, DLBCL, EBV, LMP-1, non-Hodgkin lymphoma.